Metronidazole-Induced Pancreatitis: Is There Underrecognition? A Case Report and Systematic Review of the Literature - Ibrahim Youssef; Naba Saeed; Mohammad El Abdallah; Kara Huevelhorst; Kais Zakharia (Case Reports in Gastrointestinal Medicine)
Introduction. Acute pancreatitis (AP) is the most common cause of gastroenterological hospitalization in the USA, with a mortality ranging from 5 to 20%. Up to 80% of cases are caused by cholelithiasis and alcohol abuse. Less common etiologies that need to be explored include hypertriglyceridemia, trauma, ERCP, infections, and drugs. A number of medications are known to cause acute pancreatitis, with 0.3-1.4% of all cases of pancreatitis being drug induced (DIP). Here, we present a case of metronidazole-induced acute pancreatitis. Case Summary. A 60-year-old female presented with constant severe epigastric pain associated with nausea, vomiting, and anorexia for one day. She had no past medical history of alcohol use or hypertriglyceridemia and was s/p cholecystectomy in the distant past. Symptoms had begun three days after starting metronidazole for Clostridium difficile colitis. Lipase was > 396, and CT abdomen revealed peripancreatic fat stranding. She was diagnosed with AP, metronidazole was suspected to be responsible and hence stopped, and supportive management initiated. Her symptoms improved rapidly, and pancreatic enzymes normalized within 2 days. Of note, she had had an episode of acute pancreatitis 3 years ago, also following metronidazole use, with resolution at discontinuation of the drug. She had concurrently been on omeprazole during both episodes. Discussion. Metronidazole is a commonly used antibiotic and is infrequently reported as a cause of DIP. Our review suggests the possibility of a dose-response and duration-response effect between metronidazole use and occurrence of pancreatitis. The most common presenting symptom and sign was moderate to severe epigastric pain and tenderness, accompanied by nausea/vomiting. Symptoms usually start within 2-7 days of starting the medication and usually resolve 2-5 days after discontinuation of therapy and pancreatitis treatment. The most common causative dose was 1-1.5 g/day. Our review also supports findings by Norgaard et al. suggesting that concurrent use of omeprazole potentiates the risk of metronidazole-induced pancreatitis. Conclusion. Metronidazole is a commonly used antibiotic that may cause metronidazole-induced pancreatitis, especially if patients are concurrently taking PPIs. Awareness needs to be raised amongst clinicians regarding this association, in order to correctly identify etiology of pancreatitis and discontinue metronidazole promptly when suspected as the causative factor.